The economics of trade liberalization: Charles S. Peirce and the Spanish Treaty of 1884 - James R. Wible; Kevin D. Hoover (Duke University, Center for the History of Political Economy (CHOPE), 2017)
In the 1870s and 1880s, the scientist, logician, and pragmatist philosopher Charles S. Peirce possessed an advanced knowledge of mathematical economics, having mastered and criticized Cournot as early as 1871. In 1884 he engaged in a multi-round debate with the editors of The Nation over the economics of trade liberalization in the case of a proposed trade treaty with Spain concerning import tariffs on Cuban and Puerto Rican sugar. The debate is reconstructed and related carefully both to Peirce's understanding of mathematical economics and to his philosophy of science.
Keywords: B17; B16; F10; B31; B41; 330; Charles S. Peirce; international trade; tariffs; trade policy; economic methodology; mathematical economics